(untitled) - Finley, Moses I. (Cambridge UK, 1983)
The business of politics - the vital process of conducting government through the dynamics of argument, conflict and decision-making - offers us one of the most revealing areas of insight into any society. Sir Moses Finley's exploration of politics in the city states of Greece and republican Rome yields insights into the arenas of political debate which have made a major impact on our understanding of the ancient world. The early political involvement of the free lower classes, the effect of war and conquest on political stability, and the ideological pressures which influenced the course of internal conflicts are salient themes in this stimulating investigation of the nature of government in Greece and Rome.